The inextricable link between community engagement, community based research and service learning: the case of an international collaboration Building Global Bridges project - Marks, Monique; Erwin, Kira; Mosavel, Maghboeba (South African Journal of Higher Education, 2016)
This article argues that international community based research projects, embedded in university community engagement sites, offer a dynamic learning environment. It further argues that community based learning, community engagement and service learning should be seen as allied pillars of tertiary education, using an international community based research project, Building Global Bridges, to demonstrate the value of this perspective. Drawing on the experiences of this project, that brought together students and faculty from the United States and South Africa, the article outlines multi-tiered learning benefits for community members, students from both countries, and for faculty members. It concludes by suggesting that international collaborations that centre on community based research and service learning within a community engagement context offer a beneficial framework for co-producing knowledge for higher education institutes more broadly.